THE ROLE OF WORK STRESS MEDIATION IN THE RELATIONSHIP OF MULTIPLE ROLE CONFLICT AND FEMALE EMPLOYEE PERFORMANCE - Fitri Lukiastuti; Lissa’dijah Lissa’dijah (Universitas muhammadiyah malang, 2021)
Modern life and rapid development require women to take over in developing work careers, and even some become leaders of organizations and countries. In contrast to past perceptions that place women are considered low and tend to experience discrimination in careers and jobs. The participation of women by working brings negative consequences resulting from role conflicts. This study aims to provide empirical evidence regarding the effect of multiple role conflict on the performance of female employees with job stress as a mediating variable. The sample in this study was 97 employees of Bank Jateng, the Coordinator in Purwokerto. The data analysis method uses the structural equation modeling - partial least square (SEM-PLS) with SmartPLS version 3.3.2 software. The results showed that multiple role conflicts had no effect on performance, and job stress had no effect on performance. Multiple role conflicts have a positive influence on job stress. In addition, the moderating role of job stress shows a connecting effect between the influence of multiple role conflicts on the performance of female employees